PERSONAL HYGIENE AND THE INCIDENT OF SCABIES: COMPREHENSIVE CASE MANAGEMENT AT PHC SURABAYA HOSPITAL - Harijati, Erna; Julian, Alvin (JOURNAL OF WIDYA MEDIKA JUNIOR, 2024)
Introduction: One of the risk factors for scabies is poor hygiene. Scabies is a skin condition caused by infestation and sensitization to the Sarcoptes scabiei var. hominis mite. While scabies can be treated, it is often diagnosed late, leading to delayed treatment and easy spread within groups.Objective: This paper aims to present a case of scabies in a patient who contracted the infection within the school environment, emphasizing the importance of hygiene and health awareness, particularly regarding skin health, to prevent disease transmission.Case Report: The patient presented to the Skin and Venereology Clinic at PHC Hospital with complaints of generalized itching persisting for 3 months, similar to symptoms experienced by classmates. The itching was accompanied by the presence of small ulcers. Treatment involved the application of Sulfur precipitatum Cream 10%, Krotamiton Cream 10%, and Permethrin Cream 5% once, to be left on for 8-10 hours (with a repeat application after 1 week), along with Cetirizine 10 mg.Conclusion: After weekly evaluations over 3 months, coupled with pharmacological therapy and adherence to hygiene practices, the patient returned symptom-free and without complications.